PROTECTION OF THE CIVILIAN POPULATION AS THE IMPLEMENTATION OF THE PRINCIPLE OF DISCRIMINATION - Al Qodar Purwo Sulistyo; Levina Yustinianingtyas (Universitas Muhammadiyah Malang, 2020)
Legal research aims to solve the problems that arise in connection with the application of the principle of distinction (distinction principle) in terms of the protection of civilians in international armed conflict between Israel and the Palestinians. The object of study in legal research is devoted to applying the principle of distinction against the civilian population as a victim of war under international humanitarian law in armed conflict international. To solve these problems, they need to be supported by the data in the form of legal material. The data was obtained through the study of literature and via the Internet. From this legal research to achieve results that provide answers to the problems that exist, the Israeli aggression on Palestine has violated international humanitarian law provisions and has caused misery for the Palestinian population. As a result of these actions, the Israelis may be subject to liability in the form of sanctions or punishment according to international humanitarian law provisions applicable in the international community